Using the Design Thinking Process to Co-create a New, Interdisciplinary Design Thinking Course to Train 21st Century Graduate Students - Skywark, Emily Rose; Chen, Elizabeth; Jagannathan, Vichitra (Frontiers in Public Health, 2022)
Background: Our instructional team at the [UNIVERSITY] led an innovative project that used IDEO.org’s design thinking process to create a brand-new interdisciplinary graduate course, housed in the school of public health, titled Design Thinking for the Public Good. We offer our course design process as a case study of the use of design thinking for course design. Methods: We collected data and generated insights through a variety of inspiration, ideation, and implementation design thinking methods alongside members of our three stakeholder groups: 1) faculty who teach or have taught courses related to design thinking at our higher education institution; 2) design thinking experts at ours and other institutions and outside of higher education; and 3) graduate students at our institution. Results: We learned that interdisciplinary design thinking courses should include growth-oriented reflection, explicit group work skills, and content with a real-world application. Conclusions: Our course design process and findings can be replicated to design courses regardless of area of study, level, or format.